From Confusion to Hope: Lament and Hope in the Faith of Late Adolescence and Early Adulthood - Clements, Chris D. (Journal of youth and theology, 2025)
Young people in late adolescence or emerging adulthood may re-examine their childhood Christian faith. Christian commitments in a pluralistic context can come to be regarded as one possible set of commitments among many options. Articulating clear claims about Christianity will be part of an approach to the faith nurture of young people. Yet Christian faith is also, fundamentally, an act of hope in Christ. A practice of hope, specifically among those beginning to question Christian commitments, can be the activity of lament. The Christian practice of lament addresses God amid the sorrows and confusions of this world. Christian lament is offered to God in the hope that he might respond. Ministering persons may participate in lament with young people, bringing to bear their own sense of Christian hope, and inviting young people to choose this hope as well.